Effectiveness of Butterfly Hug in Reducing Anxiety as a Psychological Adaptive Response among First-Year Nursing Students - Wahyuni Tri Lestari; Aqilah Salma Kurniasari; Esti Yunitasari (Jurnal Keperawatan Terapan, 2026)
First-year students are at risk of experiencing psychological disturbances, such as anxiety and stress, due to the adaptation process to a new environment, including nursing students. The butterfly hug is a simple self-administered technique that has the potential to effectively reduce anxiety. Roy’s Adaptation Model explains that individuals are adaptive systems that continuously interact with their environment through coping mechanisms. This study aimed to analyze the effectiveness of the butterfly hug in reducing anxiety among first-year nursing students from an adaptation theory perspective. This study employed a pre-experimental design using a one-group pretest–posttest approach. The sample consisted of 50 first-year nursing students aged 18–20 years who had experienced anxiety, selected through purposive sampling. The independent variable was the butterfly hug intervention, administered six times over two weeks, while the dependent variable was the level of anxiety. Data were collected using the Zung Self-Rating Anxiety Scale questionnaire. Statistical analysis was conducted using the Wilcoxon Signed-Rank Test with a 95% significance level. The results showed that the majority of students experienced mild anxiety prior to the intervention, whereas most reported no anxiety after the intervention. A significant reduction in anxiety levels was observed following the butterfly hug intervention (p=0.000). In conclusion, the butterfly hug is effective in reducing anxiety among first-year nursing students. This intervention functions as a cognator coping mechanism within the adaptation process, involving self-suggestion that enhances positive emotions and contributes to anxiety reduction.